2017
DOI: 10.21873/cgp.20027
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-coding RNAs and their Role in Metastasis

Abstract: Abstract.Metastasis is the major cause of death in patients with cancer. It is mediated by a multi-step process referred to as the metastatic cascade (1, 2). Initial steps include local invasion and migration, angiogenesis, epithelialmesenchymal transition (EMT) and intravasation. Tumor cells enter the circulation as single cells or circulating tumor cell clusters, are coated by platelets to escape an immune response and subsequently arrest in capillaries in distant organs as a prerequisite for extravasation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
124
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(125 citation statements)
references
References 177 publications
0
124
0
Order By: Relevance
“…HOTAIR facilitates the HOXD gene cluster for transcriptional repression by recruiting PRC2 (Rinn, et al 2007). Analysis of data in the Cancer Genome Atlas (TCGA) revealed that increased HOTAIR expression correlates with metastasis and poor prognosis in breast and prostate cancers (Weidle, et al 2017). HOTAIR is both nuclear and cytoplasmic and considered an onco-lncRNA because of its ability to promote papillary thyroid cancer (PTC) cell proliferation and silencing its expression inhibited cell growth (Zhu, et al 2016).…”
Section: Examples Of Lncrnas Dysregulated In Endocrine-related Cancersmentioning
confidence: 99%
See 2 more Smart Citations
“…HOTAIR facilitates the HOXD gene cluster for transcriptional repression by recruiting PRC2 (Rinn, et al 2007). Analysis of data in the Cancer Genome Atlas (TCGA) revealed that increased HOTAIR expression correlates with metastasis and poor prognosis in breast and prostate cancers (Weidle, et al 2017). HOTAIR is both nuclear and cytoplasmic and considered an onco-lncRNA because of its ability to promote papillary thyroid cancer (PTC) cell proliferation and silencing its expression inhibited cell growth (Zhu, et al 2016).…”
Section: Examples Of Lncrnas Dysregulated In Endocrine-related Cancersmentioning
confidence: 99%
“…Antisense oligonucleotides (ASO), liposome-delivered RNAi, vector-expressed shRNAs, and decoy RNAs or small molecules that compete for domain-domain interactions between lncRNA and proteins or within the lncRNA are of interest in targeting overexpressed lncRNAs in cancer (Weidle et al 2017). Targeting of lncRNAs using lncRNAs and nanoparticle-coated siRNAs has been successful in preclinical mouse models of BCa (Liu, et al 2015;).…”
Section: Lncrna Therapeuticsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] Originally, NF-κB interacting lncRNA (NKILA) was found to be as a lncRNA mediated by NF-κB signaling pathway inducing inflammatory cytokines such as TNF-α and IL-1β in breast cancer cell. 11 However, the role of NKILA in rectal cancer was still unclear. 11 However, the role of NKILA in rectal cancer was still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Recent study showed non-coding RNAs (ncRNAs) are transcribed from non-protein-coding DNA sequences and key regulatory RNAs. 5 Long non-coding RNAs (LncRNAs) belong to ncRNAs that are longer than 200 nucleotides in length. 6 Previous studies suggested that the lncRNAs acted as transcriptional modulator, splicing regulator, post-transcriptional processor, enhancer, molecular decoys for miRNAs, chromatin remodeler, a guide for protein-protein, protein-DNA and protein-RNA interactions.…”
mentioning
confidence: 99%